Stability analysis and internal heating effect on oscillatory convection in a viscoelastic fluid saturated porous medium under gravity modulation from the history of conferences on the machine and mechanism science - Bhadauria, Beer Singh; Singh, Manoj Kumar; Singh, Ajay; Singh, Brajesh Kumar; Kiran, Palle (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we investigate the combined effect of internal heating and time periodic gravity modulation in a viscoelastic fluid saturated porous medium by reducing the problem into a complex non-autonomous Ginzgburg-Landau equation. Weak nonlinear stability analysis has been performed by using power series expansion in terms of the amplitude of gravity modulation, which is assumed to be small. The Nusselt number is obtained in terms of the amplitude for oscillatory mode of convection.
Keywords: Non-linear stability analysis; complex Ginzburg-Landau equation; gravity modulation; internal heating; bifurcations